1994
DOI: 10.1080/00207549408957032
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of production ordering systems

Abstract: The flexibilityof production ordering systems as medium range production control systems are studied. The changes affecting flexibility, production ordering systems as responses to changes, and the performance measures of flexibility are clarified. On the basis of this framework, mathematical models of production system and production ordering systems are developed to evaluate their flexibility. Two types of changes are considered: demand fluctuation and downtime fluctuation due to machine breakdown, and two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This effect has been studied extensively, both from industrial and theoretical points of view, and multiple causes have been mentioned in the literature (Forrester 1969, Muramatsu et al 1985, Takahashi et al 1994, Wu and Meixell 1998, Lee et al 2000, Warburton 2004, Sterman 2006. Indeed, it has been argued that flexibility in a supply chain increases when the bullwhip effect is reduced, reflecting how well a management method adapts the inventory and production variability to the demand variability (Muramatsu et al 1985, Takahashi et al 1994. Exploring this idea, Pereira (1999) found general expressions for amplification in the case of push, pull and hybrid ordering methods.…”
Section: Introductionmentioning
confidence: 98%
“…This effect has been studied extensively, both from industrial and theoretical points of view, and multiple causes have been mentioned in the literature (Forrester 1969, Muramatsu et al 1985, Takahashi et al 1994, Wu and Meixell 1998, Lee et al 2000, Warburton 2004, Sterman 2006. Indeed, it has been argued that flexibility in a supply chain increases when the bullwhip effect is reduced, reflecting how well a management method adapts the inventory and production variability to the demand variability (Muramatsu et al 1985, Takahashi et al 1994. Exploring this idea, Pereira (1999) found general expressions for amplification in the case of push, pull and hybrid ordering methods.…”
Section: Introductionmentioning
confidence: 98%
“…This effect has been extensively studied, both from industrial and theoretical points of view (Takahashi et al, 1994). Among the multiple reasons mentioned in literature (Lee et al, 2000;Takahashi et al, 1994;Warburton, 2004;Wu and Meixell, 1998), four features are frequently reported at the origin of this phenomenon (Lee et al, 1997): demand signal processing, strategic ordering behavior, ordering batching and price variations. Geary et al (2006) pointed out ten common causes of bullwhip-effect and the subsequent re-engineering principles to eliminate or prevent amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Under some conditions, pull type production ordering systems are more flexible than are push type systems. However, a simulation study demonstrated that the influences of downtime fluctuation makes a push-type production ordering system more flexible than a pull-type system (Takahashi, et al, 1994).…”
Section: Other Theoretical Constructs Related To Flexibilitymentioning
confidence: 99%
“…Pull-type production systems calculate production order on the basis of feedback information and the actual production quantity of the succeeding operation or stage in the production process (Takahashi, et al, 1994). Demand originates at the end of the production process, so that information flows from the end to the beginning.…”
Section: Other Theoretical Constructs Related To Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation